(untitled) (Boca Raton, Fl., 2003)
"Chemical and functional properties of food saccharides" servees as a veritable handbook on the chemistry of carbohydrates. This substantial compilation focuses on saccharides as food constituents by explaning their structural chemistry, sources, applications, and nutritional properties.
Keywords: Sweeteners